Determination of optimal parameters in the protocol for total genomic dna isolation from blood sample of the jamnapari goats - Chung, Miaw Ling. (Universiti Malaysia Sarawak (UNIMAS), 2010)
Jamnapari goat (Capra hircus) is an important economic goat breed originated from India with high milk-and-meat production. Genetic profiling is important for the verification and characterization of Jamnapari goat breed. A pre-requisite for successful implementation of these genetic resourcing methods is the ability to isolate a good amount of high quality total genomic DNA. Therefore, a reliable method producing good yield of high molecular weight DNA from blood samples is essential and required for downstream analysis. This study was conducted to determine the optimal parameters influencing the total genomic DNA extraction from blood samples of Jamnapari goats. The parameters studied included methods of extractions, incubation temperatures and time towards the quantity and quality of DNA extracted from blood. The DNA obtained from each parameter tested were amplifiable with cytochrome b primers giving a product size at a range of 300-400bp. The DNA sequence analysis showed that the products obtained were 99% identical to the sequences of Jamnapari goats. Analysis of variance showed that there were no significant differences between the phenol-chloroform method and salting-out method for DNA extractions. The optimal level of parameters for DNA extraction from whole blood sample of Jamnapari goat was by Salting-Out method with incubation temperature of sample digestion at 55°C and incubation time of 2 hours.